2022
DOI: 10.1186/s12884-022-04881-y
|View full text |Cite
|
Sign up to set email alerts
|

Parenting sense of competence and its predictors among primiparous women: a longitudinal study in China

Abstract: Background Parenting sense of competence significantly affects the quality of parenting behaviours and healthy infant development. However, primiparous women without parenting experience may lack confidence and feel stress. This study aimed to explore the status of parenting sense of competence and identify its predictors among primiparous women. Methods A longitudinal study design was used. Primiparous women were recruited by using a convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…The encouragement, support and backing of the professionals involved fosters feelings of competence and self-efficacy which, in themselves, also promote confidence and security, which are essential for establishing and maintaining breastfeeding. 20,24,25 Limitations were found in this study. After analyzing the variables and their significance, it is suggested that larger-scale studies should be carried out to see if they would translate into different results, as is the case in other similar studies.…”
Section: Discussionmentioning
confidence: 73%
“…The encouragement, support and backing of the professionals involved fosters feelings of competence and self-efficacy which, in themselves, also promote confidence and security, which are essential for establishing and maintaining breastfeeding. 20,24,25 Limitations were found in this study. After analyzing the variables and their significance, it is suggested that larger-scale studies should be carried out to see if they would translate into different results, as is the case in other similar studies.…”
Section: Discussionmentioning
confidence: 73%
“…O incentivo, suporte e apoio dos profissionais envolvidos, fomenta sentimentos de competência e autoeficácia que por si, também são promotores de confiança e segurança, imprescindíveis para o estabelecimento e manutenção da amamentação. 20,24,25 Foram encontradas limitações no presente estudo. Após análise das variáveis e da sua significância, sugere-se a realização de estudos de uma maior escala, para perceber se estes se traduziriam em resultados diferentes, tal como sucede noutros estudos semelhantes.…”
Section: Discussionunclassified
“…This may be because the physical and mental demands of parenting change as the child develops 53. Chinese primiparous women have relatively good parenting competence at 3 months postpartum 54. Later into the postpartum period, the women were able to better choose appropriate and regular feeding patterns, recognise their baby’s needs, and soothe their crying or upset baby.…”
Section: Discussionmentioning
confidence: 99%
“…53 Chinese primiparous women have relatively good parenting competence at 3 months postpartum. 54 Later into the postpartum period, the women were able to better choose appropriate and regular feeding patterns, recognise their baby's needs, and soothe their crying or upset baby. Hence, postpartum stress associated with infant nurturing was reduced, and it only increased if the baby developed any health issues.…”
Section: Discussionmentioning
confidence: 99%